2013
DOI: 10.4209/aaqr.2012.11.0313
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Concerns on the Use of Ozone Scrubbers for Gaseous Carbonyl Measurement by DNPH-Coated Silica Gel Cartridge

Abstract: ABSTRACT2,4-Dinitrophenylhydrazine (DNPH) is a typical derivatizing agent coated on sorbent cartridges for detection of carbonyl compounds at ambient levels. However, airborne oxidant of ozone (O 3 ) can react with DNPH to form side products that can interfere with the accurate detection of carbonyls. It is the most critical interferer degrading carbonyl-DNP-hydrazone formed on the cartridge during sampling, resulting in underestimation of carbonyl concentrations; this strong oxidant can be removed by installi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…A Whatman Teflon filter assembly (Clifton, NJ) and a Waters Sep-Pak ozone scrubber were installed in front of the cartridge to remove any air particle and prevent oxidization from ozone effect, respectively (Spaulding et al, 1999). The collection efficiency and recovery of carbonyls would not be impacted by the ozone scrubber (Ho and Yu, 2002;Ho et al, 2013a). The sampling reproducibility (> 95%) was assessed by collection of collocated field samples.…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…A Whatman Teflon filter assembly (Clifton, NJ) and a Waters Sep-Pak ozone scrubber were installed in front of the cartridge to remove any air particle and prevent oxidization from ozone effect, respectively (Spaulding et al, 1999). The collection efficiency and recovery of carbonyls would not be impacted by the ozone scrubber (Ho and Yu, 2002;Ho et al, 2013a). The sampling reproducibility (> 95%) was assessed by collection of collocated field samples.…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…Potential drawbacks existed in the method for sampling air carbonyls using DNPH-coated silica cartridges, mainly including: (1) ambient O 3 was the critical interference using DNPH-coated solid sorbent cartridges; (2) environmental relative humidity could inhibit derivatization kinetics and contributed to degradation of carbonyl-DNPH derivatives during sampling (Saha et al, 2012;Ho et al, 2013); (3) sampling volume and concentration also influenced the analysis of carbonyls using DNPH cartridges (Pal and Kim, 2008a); (4) unsaturated carbonyls such as acrolein were not accurately quantified using the DNPH method (Ho et al, 2011); and (5) the HPLC method was reliable for low-weight carbonyls, while gas chromatography was more suitable for high-weight carbonyls (Pal and Kim, 2008b;Kim and Pal, 2010;Pang et al, 2011;Xie et al, 2013). However, these potential drawbacks could be minimized though the experiments of quality assurance in the method (Feng et al, 2005;Lü et al, 2010).…”
Section: Samplingmentioning
confidence: 99%
“…In this study, to ensure the reliability of air sampling and minimize the biases caused by the drawbacks above, the breakthrough experiment by connecting two cartridges in series was conducted before sampling, and no carbonyls were detected in the back cartridge when sampling time was 2 h at a flow rate of 2 L/min; cartridge collection efficiency (CE) experiment showed that over 99% of carbonyls were recovered by the first cartridge, indicating the complete recovery of all carbonyls (Table 1); a potassium iodide (KI) denuder was connected to the upstream of the cartridges to avoid the interference of ambient O 3 (Lü et al, 2010;Ho et al, 2011;Duan et al, 2012;Ho et al, 2013); other experiments of quality assurance and detail sampling procedure were described by our previous reports (Feng et al, 2005;Lü et al, 2010;Duan et al, 2012). Based on these experiments, air samples was collected form October 2011 to July 2012 in one site in urban center in Qinzhou, which was located on the roof of a building (~35 m above ground level), and surrounded by roads, buildings and offices (Fig.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Atmospheric carbonyl compounds (CCs) are oxygenated volatile organic compounds, receiving worldwide attention (Andreini et al, 2000;Bakeas et al, 2003;Cavalcante et al, 2006;Pal et al, 2008;Uchiyama et al, 2012;Ho et al, 2013) since the last few decades. They are ubiquitous and are responsible for the degradation of poor air quality through the formation of tropospheric ozone and peroxy acetyle nitrate which in turn forms photochemical smog.…”
Section: Introductionmentioning
confidence: 99%